Spekulation mit Agrarrohstoffen: Eine Replik - Ingo Pies (Wirtschaftsdienst, 2015)
In der Juniausgabe 2015 veröffentlichte der Wirtschaftsdienst einen Aufsatz von Christian A. Conrad über "Die Auswirkungen der Spekulation mit Nahrungsmitteln und Rohstoffen". Nach einer Replik von Ingo Pies hierzu eine Erwiderung von Christian A. Conrad. – – The reply of Ingo Pies explains the background of the public quarrel over agricultural speculation and criticises three points which may hinder a productive debate. Christian Conrad responds that due to problems of methodology, investigations using econometrics can neither prove nor disprove any infl uence of speculation on prices, and he warns against drawing the wrong conclusions from the empirical studies.
Keywords: F55; G13; Q11; Q31; 330